Challenging the miracle of transgenic crops in China: findings from a case study in cotton using panel data - Diemuth E. Pemsl; Marc Völker; L. Wu; Hermann Waibel (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
Bt cotton has been cultivated in China for the past 10 years. Limitations of previous studies analyzing the impact of this technology are the short time period considered and lack of panel data. In this paper, we present findings from monitoring 150 Bt cotton farmers in 2002 and 2005. Descriptive analysis reveals that pesticide use is increasing while seed price and Bt toxin concentration decreased. The Bt variable was consistently insignificant in a production function with damage control specification model and in a fixed effects model. There is indication that poor standards in pesticides and Bt cotton varieties can cause this result.
Keywords: 330; Biotechnology; Bt cotton; productivity analysis; panel data; Asia; China